Health as an element of a quality of labour life - T. V. Khlopova (Acta Biomedica Scientifica)
In article the emphasis is placed on one of the most important elements of the labor potential, characterizing quality of labor human life, - health. Being a basis of a labor potential of the worker, at the same time health is a factor which action is beyond communication of losses of working hours with an incidence. In the conditions of ecology deterioration increases the probability of the torn health of future generations. Many of modern types of diseases, including professional diseases, for a long time bring people out of an able-bodied condition, and quite often result in disability. The technical, organizational, socio-economic and cultural factors influencing indicators of employee's health at the enterprises are considered. Ambiguous nature of influence of these factors is noted.